Selection for super traits or sub indices: A practical approach for dairy sheep - Barillet F.; Marie C.; Astruc J.M. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
In France, efforts in research and extension for dairy sheep genetics have been focused for the last 30 years on the design and implementation of breeding programs of the French local breeds in their specific area of production. The main goal was to improve the milk yield genetic level of these breeds in the framework of feeding systems based on the use of high quantities of roughage to increase the self-sufficient production of the farms and to account for the regulations of the brand name cheeses. This first objective has actually been reached (especially for the Lacaune breed). Under these conditions, the new objectives in the future will focus on increasing the selection intensity on milk composition and functional traits with the aim of maintaining this production in mountain areas. Thus, research on secondary traits regarding milk traits has been increasing in recent years. A way to construct total indices for dairy sheep based on sub index or super traits is discussed in this paper.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)